Predictions of α decay half-lives for even–even superheavy nuclei with 104 ≤ Z ≤ 128 based on two-potential approach within cluster-formation model - Liu, Hong-Ming; Xu, Jun-Yao; Deng, Jun-Gang; He, Biao; Li, Xiao-Hua (International journal of modern physics. E, Nuclear physics, 2019)
In this work, we systematically study the α decay half-lives of 170 even–even nuclei with 6 0 ≤ Z ≤ 1 1 8 within the two-potential approach while the α decay preformation factor P α is obtained by the cluster-formation model. The calculated results can well reproduce the experimental data. In addition, we extend this model to predict the α decay half-lives of 64 even–even nuclei with 1 0 4 ≤ Z ≤ 1 2 8 whose α decay is energetically allowed or observed but not yet quantified. For comparison, the two famous models i.e., SemFIS proposed by Poenaru et al. [Europhys. Lett. 77 (2007) 62001] and UDL proposed by Qi et al. [Phys. Rev. Lett. 103 (2009) 072501] are used. The predicted results of these models are basically consistent. At the same time, through analyzing the changing trend of α decay energy Q α of Z = 1 1 8 , 1 2 0 , 1 2 2 , 1 2 4 , 1 2 6 and 128 isotopes nuclei with the increasing of neutron number N and that of α decay preformation factor P α of those isotopes even–even nuclei with the increasing of neutron number N, N = 1 7 8 may be a new neutron magic number.